The Republic of Latvia : Financial System Stability Assessment, including Reports on Observance of Standards and Codes on the following topics; Banking Supervision; Payment Systems; Securities Regulation; Insurance Regulation; Corporate Governance; and Monetary and Financial Policy Transparency. (IMF Staff Country Reports; Country Report, 2002)
This paper presents key findings of Latvia's Financial System Stability Assessment, including Reports on Observance of Standards and Codes on Banking Supervision; Payment Systems; Securities Regulation; Insurance Regulation; Corporate Governance; and Monetary and Financial Policy Transparency. The assessment reveals that the banking system of Latvia is well capitalized, profitable, and liquid following its recovery from the effects of the Russian crisis in 1998. A notable feature of the financial system is the significant share of nonresident deposits and foreign equity in the banking system and nonresident investment in the securities market.